Analisis Penerapan Kurikulum 2013 dalam Meningkatkan Prestasi Belajar Siswa di MTs Al Ittihadiyah Laut Dendang - Neliwati, Neliwati; Harahap, Halimatussakdiah; Marpaung, Khairun Nisa; Harahap, Nur Fauziah (MODELING: Jurnal Program Studi PGMI, 2023)
The implementation of the 2013 curriculum requires teachers to professionally design effective and meaningful (fun) learning, organize learning, choose the right approach, determine learning procedures and build competence effectively, and set success criteria. In implementing the 2013 Curriculum, learning achievement can be integrated into all learning in every field of study contained in the curriculum. This makes teachers who have used traditional evaluations have to change their evaluations, namely to become authentic evaluations based on curriculum demands. In accordance with the problem, this study aims to analyze "How to Apply the 2013 Curriculum in Improving Student Achievement at MTs Al-Ittihadiyah Laut Dendang". The method used is to use a descriptive method to find out the planning and implementation of the 2013 curriculum carried out by the teacher in implementing and increasing student achievement.